1998
DOI: 10.1016/s0029-7844(98)00056-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Chorioamnionitis and the Prognosis for Very Low Birth Weight Infants

Abstract: Our results suggest a link between clinical chorioamnionitis and several indices of neonatal morbidity in the very low birth weight infant. Chorioamnionitis appears to make the very low birth weight infant particularly vulnerable to neurologic damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0
4

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(53 citation statements)
references
References 12 publications
2
47
0
4
Order By: Relevance
“…An almost universal finding in most studies is the increased risk of EONS, both in clinical and histological chorioamnionitis [6,10,16,24,25,26]. In our study the incidence of EONS was significantly higher among infants exposed to maternal clinical chorioamnionitis, and this association persisted after adjusting for GA, birth weight, and all other confounders.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…An almost universal finding in most studies is the increased risk of EONS, both in clinical and histological chorioamnionitis [6,10,16,24,25,26]. In our study the incidence of EONS was significantly higher among infants exposed to maternal clinical chorioamnionitis, and this association persisted after adjusting for GA, birth weight, and all other confounders.…”
Section: Discussionsupporting
confidence: 67%
“…While clinical chorioamnionitis has been considered an important risk factor for RDS [10], Watterberg et al [4] showed that histological chorioamnionitis can stimulate lung maturation, reducing the incidence of acute RDS but increasing lung susceptibility to postnatal damage when exposed to other potential noxious factors. An important issue to consider when referring to this morbidity is the effect of antenatal steroid administration [11] that, in fact, was not widely used when the above-mentioned studies were conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The risk of systemic fetal inflammation and chorioamnionitis is inversely related to gestational age [17,18]. We present a retrospective clinical study analyzing serum IL-6, coagulation profile and development of IVH in a cohort of preterm infants born with 23 0/7 to 27 6/7 weeks of gestational age.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on preterm infants demonstrated an association of histopathologically confirmed chorioamnionitis and funisitis with the development of IVH [17,18,19,20,21]. Vergani et al [19] even reported a dose-dependent relationship between severity of acute placental inflammatory lesions and the severity of IVH.…”
Section: Discussionmentioning
confidence: 99%